Determination of Tetracycline on the Surface of a High- Performance Graphene Modified Screen-Printed Carbon Electrode in Milk and Honey Samples - Filik, Hayati; A. Avan, Asiye; Aydar, Sevda; Ozyurt, Dilek; Demirata, Birsen (Current Nanoscience, 2016)
Background: Three tetracycline antibiotics (TCs), tetracycline (TC), oxytetracycline (OTC), and chlortetracycline (CTC), were extensively employed in human, veterinary medicine as well as feed additives to treat and prevent bacterial infections. Tetracycline antibiotics are widespectrum antibiotics active versus a wide range of gram-positive and gram-negative bacteria, as well as a range of organisms such as mycoplasma and chlamydia. As mentioned above, these drugs stay as residues in animals, fish, and birds are harmful to humans at quite low levels. Thus, it is important to develop an effective alternative procedure for the detection of tetracycline compounds. Methods: An electrochemical sensor based on the electrocatalytic activity of commercial screen-printed graphene electrode for sensitive detection of tetracycline was presented. The electrochemical behaviors of tetracycline on graphene screen-printed carbon electrodes (GRSPCEs) were researched by cyclic voltammetry and differential pulse voltammetry. The use of the commercially disposable graphene modified screen-printed carbon electrode for milk and honey sample assays obtained satisfactory results, which made it an encouraging alternative in routine sensing applications. Results: This study focuses the first application of GR modified SPCE as voltammetric sensors for the detection and quantification of TC. The large advantages of this type of sensor system are associated with their modest cost, potential portability, the simplicity of operation, reliability, and the compact detector arrangement containing the working electrode, auxiliary and reference electrodes. This sensor features speedy experimentation time, well suitability for field trace TC analysis and an admissible sensor lifetime. This proposed electrochemical approach was successfully adapted to determine the TC in honey and milk samples. Conclusions: The results suggest that the method developed for the determination of TC using GR modified SPCE is practicable for the sensing of the antibiotic at 0.08 μM levels with really good precision. This approach allows avoiding the electrode fouling that is noticed when evaluating this class of compound. The process, therefore, is very convenient for the daily routine assessment of tetracycline antibiotics. The proposed voltammetric approach is highly competitive for the detection of these antibiotics in foods, particularly as a screening method. It was not necessary to use solid phase extraction, we usually employ for a preliminary separation when assaying milk and honey samples.
Keywords: tetracycline